Biofortification: A food-systems solution to help end hidden hunger - HarvestPlus; Food and Agricultural Organization of the United Nations (HarvestPlus, 2019)
The objective of the brief, Biofortification: A food-systems solution to help end hidden hunger, is to “encourage the adoption and scaling up of biofortification through national policies and programs, with collaborative support from FAO and HarvestPlus,” according to the Introduction. The brief has been distributed to staff of both organizations and is also available publicly to inform policy, program, and advocacy work.